Rediscovering MIF: New Tricks for an Old Cytokine. Issue 5 (May 2019) - Harris, James; VanPatten, Sonya; Deen, Nadia S.; Al-Abed, Yousef; Morand, Eric F.
Abstract : Produced by many cell types, macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine with critical and supporting roles in many disease states and conditions. Its disease associations, myriad functions, receptors, and downstream signaling have been the subject of considerable research, yet many questions remain. Moreover, the relevance of MIF's partially functionally redundant family member, D-dopachrome tautomerase (D-DT), also remains to be further characterized. Here, we discuss recent discoveries demonstrating direct roles of MIF in supporting NLR Family Pyrin Domain-Containing 3 (NRLP3) inflammasome activation, as well as acting as a molecular chaperone for intracellular proteins. These findings may offer new clues to understanding MIF's multiple functions, and assist the development of putative MIF-targeting therapeutics for a variety of pathologies. Highlights: Originally characterized as a cytokine, MIF has both extracellular and intracellular functions, with roles in immune as well as non-immune cells. A second MIF family protein, D-DT, shares some functions with MIF, but remains to be fully investigated. MIF was recently shown to specifically regulate the activation and assembly of the NLRP3 inflammasome. MIF has also been found to act as a molecular chaperone, regulating the deposition of misfolded Cu/Zn superoxide dismutase 1 (SOD1) on mitochondria and endoplasmic reticulum in ALS. MIF may also act as a chaperone to stabilize the activity of insulin.